If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(4r + 6) + r = -5r + -36 Reorder the terms: -6(6 + 4r) + r = -5r + -36 (6 * -6 + 4r * -6) + r = -5r + -36 (-36 + -24r) + r = -5r + -36 Combine like terms: -24r + r = -23r -36 + -23r = -5r + -36 Reorder the terms: -36 + -23r = -36 + -5r Add '36' to each side of the equation. -36 + 36 + -23r = -36 + 36 + -5r Combine like terms: -36 + 36 = 0 0 + -23r = -36 + 36 + -5r -23r = -36 + 36 + -5r Combine like terms: -36 + 36 = 0 -23r = 0 + -5r -23r = -5r Solving -23r = -5r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '5r' to each side of the equation. -23r + 5r = -5r + 5r Combine like terms: -23r + 5r = -18r -18r = -5r + 5r Combine like terms: -5r + 5r = 0 -18r = 0 Divide each side by '-18'. r = 0 Simplifying r = 0
| 18/0.06 | | 6(7-2p)=3(5p-1) | | -18h+12=7-18h | | s^2-26s=11 | | 4x^2=4/9 | | -13r-20-7r=-10+20 | | 8a-3=6a+17 | | 3(x+9)-7=x+10 | | -4p+6=1+p | | 4x/334+(678x+1)=4 | | -(8y-6)-(-7y-7)=4 | | 18y=18y-15 | | h^2-28h-47=0 | | v^2-8=0 | | -5n-32/3=-13/4(13/4n+1) | | 7z+8=2d-7 | | 529+474= | | (t+42)/3=(t+126)/7 | | 5x=12+2+6 | | 2x^1/3=x^-2/3 | | x=3(x+1)-2x | | -11.82+0.8k=2.9k+18.42 | | 2y-1=17 | | y=-2-5y+7y-2(4y-7) | | 1+3n=6n+4 | | 1/2+3/4z=-5/2 | | 15-12x=2x+13 | | 9x-4=7x-1 | | 9x-4+7x-1= | | E=ex | | k^2+4k+4=-7 | | 5(a-4)=6(a-7) |